Substation arrangement: a literature review study (Research, Society and Development, 2021)
Electric energy plays a fundamental socio-economic role in the world. In this context, substations are of great importance since they are used to direct the flow of energy in a power system and enable its diversification through alternative routes and also allow the distribution of electricity to serve residential consumers, commercial and industrial at the appropriate level for use. The growing demand for electricity and consequently the expansion of the electrical system has contributed to the increase in studies in the area. This work presents a bibliographical study, from a bibliometric analysis, of the researches developed in the area of substation arrangement. Literature review is an important tool to raise scientific production on the subject. For this study, academic productions from undergraduate and graduate courses, journal articles and publications in conferences on the Scopus and Capes Periodicals platforms were considered due to their scope, organization of data and relevance. The research results indicate the most current and the main researches in the area of substation arrangement. Regarding the countries that have published the most in the last 5 years about the arrangement of substations, China stands out, which is in first place with 14 publications. Brazil occupies the sixth position in related productions on the subject.